2014
DOI: 10.1007/s11999-014-3495-z
|View full text |Cite
|
Sign up to set email alerts
|

Complications Associated With the Initial Learning Curve of Minimally Invasive Spine Surgery: A Systematic Review

Abstract: Background There is an inherently difficult learning curve associated with minimally invasive surgical (MIS) approaches to spinal decompression and fusion. The association between complication rate and the learning curve remains unclear. Questions/purposes We performed a systematic review for articles that evaluated the learning curves of MIS procedures for the spine, defined as the change in frequency of complications and length of surgical time as case number increased, for five types of MIS for the spine. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
173
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(181 citation statements)
references
References 26 publications
5
173
2
1
Order By: Relevance
“…The median registration error was 0.6 mm (range, 0.3-1.1 mm). This error is similar to that observed in previous publications [1,2,10,17,21,22]. In our study, the amount of registration error did not improve overtime (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The median registration error was 0.6 mm (range, 0.3-1.1 mm). This error is similar to that observed in previous publications [1,2,10,17,21,22]. In our study, the amount of registration error did not improve overtime (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…However, some papers have reported problems related to the use of navigation, including increased operative time as a result of the additional technological complexity; in addition, there is no evidence of which we are aware suggesting that navigation decreases the risk of local recurrence [7,16]. It seems to us that for a tool of this sort, the learning curve needs to be considered [12,17], but to our knowledge, the results of navigation in orthopaedic oncology have not been assessed as a function of surgical experience (number of procedures performed). In this study, we analyzed common problems related with this procedure, surgical time, resection accuracy, and histological margins with a particular focus on how surgical time and accuracy changed during the first 2 years (78 cases) of our experience with this new technology.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A significant learning curve has been demonstrated when learning a new surgical technique in a number of publications, especially those related to neurological injury. 26,29,32 We would propose that the same learning curve would not necessarily exist with the adoption of the Wiltse approach for 2 reasons. First, the Wiltse approach allows excellent visualization of the lateral bony anatomy and safe landmarks are readily identified.…”
Section: Discussionmentioning
confidence: 99%
“…Cited factors for nonadoption of MIS techniques include technical factors, limited training opportunities, and increased radiation exposure [74]. Specifically, the lack of training opportunities can lead to a steep learning curve, where earlier cases in a surgeon's experience may be associated with worse operative and clinical outcomes [75][76][77]. Studies investigating the learning curve in MIS techniques have identified earlier cases to be associated with increased operative times, radiation exposure, and complication risk [76][77][78].…”
Section: Limitations To Mis Utilization: the Learning Curvementioning
confidence: 99%